Rwanda: The Rubaya community gene bank - Dusengemungu, Leonidas; Ndacyayisenga,Theophile; Otieno, Gloria Atieno; Ruzindana Nyirigira, Antoine; Rwihaniza Gapusi, Jean (Routledge, 2015)
The Rubaya community gene bank, located in the Rubaya sector of Gicumbi district in Northern Rwanda, is managed by the Kundisuka cooperative. It originated when a farmer by the name of Mpoberabanzi Silas and an agronomist working in the Rubaya sector recognized the need to preserve some of the genetic resources in the area that were being lost (e.g. several varieties of beans, peas, maize, wheat and sorghum). Implementation of the project was supported by the staff of the Rwanda Agriculture Board (RAB) in cooperation with Bioversity International (Plate 18). The managing cooperative was created in September 2012 and consists of about ten members with Mpoberabanzi Silas as president. The community gene bank’s storage facilities were constructed locally with support from Vision 2020’s Umurenge Program and the Ministry of Local Government. Their main purpose is to store the region’s priority crops (maize, wheat, beans and Irish potatoes), but farmers are free to use the facilities to store and conserve other seeds and planting material. The community gene bank does not yet have a visible role in the community, for example, in seed production or participatory crop improvement, as it is still in its early stages. However, its members’ vision is to invest in seed multiplication to make good-quality seeds available to the local community and regional gene banks. This will transform the enterprise into a business-oriented farmer cooperative certified by RAB.